Transformation of Mediation in Islamic Law: Analysis of Principles, Mechanisms, and Implications for Dispute Resolution - Maria Rosalina; Muhammad Arifin; Farid Wajdi (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2025)
This study aims to analyze the transformation of mediation in Islamic law from classical to contemporary times and to assess the alignment of modern mediation practices with sharia principles. Mediation in the Islamic legal tradition is rooted in the concepts of ṣulḥ and iṣlāḥ, which emphasize dispute resolution through peace, deliberation, and substantive justice. Along with the development of modern legal systems, mediation has undergone a process of institutionalization and formalization within the framework of positive law, including in the judicial systems of Muslim countries. This study uses a normative legal research method with a statutory, conceptual, and historical approach. Legal sources include the Qur'an, hadith, classical fiqh literature, legislation, and relevant legal doctrines. The results show that the transformation of mediation is evolutionary, characterized by changes in form and mechanisms without eliminating the basic principles of justice, voluntariness, and benefit. Contemporary mediation practices are fundamentally aligned with the principles of Islamic law, particularly in their orientation toward peace and restorative dispute resolution. The main challenge lies in implementation, particularly in maintaining the substance of sharia values so that they are not diminished by procedural formalism. Therefore, strengthening the integration of Islamic legal ethics and modern mediation professional standards is key to realizing an effective, fair, and civilized dispute resolution system.